'n Voorgestelde raamwerk vir die literatuurstudie as kwalitatiewe navorsings-metodologiese tegniek: 'n literatuurstudie oor genadedood as voorbeeld uit die teologiese etiek - L. O. K. Lategan (Acta Theologica)
This article proposes a framework on how to conduct a literature study as part of the research process. Seven steps form the design of this framework, namely the identification of the scientific ethos; the identification of both the research problem and the research project; the conceptualisation of key concepts; the analysis of material on the research topic; a reflection on the literature study; a critique on the existing body of literature related to the research problem, and the formulation of an opinion. Euthanasia serves to illustrate the application of this framework.